2022
DOI: 10.1371/journal.pone.0249151
|View full text |Cite
|
Sign up to set email alerts
|

Stage-differentiated ensemble modeling of DNA methylation landscapes uncovers salient biomarkers and prognostic signatures in colorectal cancer progression

Abstract: Background Aberrant DNA methylation acts epigenetically to skew the gene transcription rate up or down, contributing to cancer etiology. A gap in our understanding concerns the epigenomics of stagewise cancer progression. In this study, we have developed a comprehensive computational framework for the stage-differentiated modelling of DNA methylation landscapes in colorectal cancer (CRC). Methods The methylation β-matrix was derived from the public-domain TCGA data, converted into M-value matrix, annotated w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…A previous study have identified that DYNC1H1, GRIN2A, and GRM1 as new driving genes for CRC stage II progression, IGF1R, CPS1, SPTA1, and DSP as new hub driving genes for CRC stage III progress, and GSK3B, GGT1, and EIF2B5 as new hub driving genes for CRC stage IV. 32 Sangeetha Muthamilselvan et al 33 found that FBN1 as a stage I-salient hyper methylated gene, FOXG1 as a stage II-salient hyper methylated gene, HCN1 as stage III-salient hyper methylated gene, and NELL1, ZNF135, FAM123A, LAMA1 as stage IV-salient hyper methylated genes, which would drive the progression of CRC. Ashok Palaniappan and Sarathi 34 reported that CRLF1, CALB2 as stage I-specific differentially expressed genes (DEGs), GREM2, ADCY5, PLAC2, and DMRT3 as stage II-specific DEGs, PIGR and SLC26A9 as stage III-specific DEGs, and GABRD, DLX3, CST6, and HOTAIR as stage IV-specific DEGs, which were identified as progression-significant biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study have identified that DYNC1H1, GRIN2A, and GRM1 as new driving genes for CRC stage II progression, IGF1R, CPS1, SPTA1, and DSP as new hub driving genes for CRC stage III progress, and GSK3B, GGT1, and EIF2B5 as new hub driving genes for CRC stage IV. 32 Sangeetha Muthamilselvan et al 33 found that FBN1 as a stage I-salient hyper methylated gene, FOXG1 as a stage II-salient hyper methylated gene, HCN1 as stage III-salient hyper methylated gene, and NELL1, ZNF135, FAM123A, LAMA1 as stage IV-salient hyper methylated genes, which would drive the progression of CRC. Ashok Palaniappan and Sarathi 34 reported that CRLF1, CALB2 as stage I-specific differentially expressed genes (DEGs), GREM2, ADCY5, PLAC2, and DMRT3 as stage II-specific DEGs, PIGR and SLC26A9 as stage III-specific DEGs, and GABRD, DLX3, CST6, and HOTAIR as stage IV-specific DEGs, which were identified as progression-significant biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the transcriptomic stage-specific patterns of colorectal cancer samples identified here with their methylomic stage-specific patterns [53], we uncovered interesting connections. Some of the stage-salient genes here were also identified as stage-specific differentially methylated genes, namely: BAI3, TPM2, ZSCAN18, ZNF415 (Stage-I); PLAC2, DMRT3 (Stage-II); PIGR, TUBAL3 (Stage-III); and CST6 (Stage-IV).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies indicate stage-specific 51 and age-specific 52 effects of DNA methylation in certain genes on the survival outcomes of CRC patients. These results clearly suggest heterogeneity in the overall survival time of patients with CRC.…”
Section: Methodsmentioning
confidence: 99%